Development of Lightweight Geopolymer Composites and their Structural Applications - Li, Zhixing (Curtin University, 2022)
This thesis presents the development of ambient-cured lightweight geopolymer composites (LGCs) and their quasi-static and dynamic material properties. New lightweight reinforced panels made of the developed LGCs are proposed for structural applications. Structural performances of the developed LGC panels are investigated under bending, punching shear and windborne debris impact loads. The outcomes derived from this study can be used in the design of LGC materials and lightweight panels against static and dynamic loads.